2022
DOI: 10.1039/d2py00235c
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of new bio-based antibacterial acrylic bone cementviamodification with a biofunctional monomer of nitrofurfuryl methacrylate

Abstract: Polymethyl methacrylate (PMMA) bone cement is commonly used filling material in orthopedic surgery. The excellent performance, such as convenient handling and rapid self-hardening feature makes it the most widely used....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 86 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…Leaching experiments demonstrated that this bone cement did not release antibacterial components, yet it exhibited effective antibacterial properties against common clinical bacteria [ 14 ]. Similarly, Fu et al [ 16 ] developed a non-leaching antibacterial bone cement using nitrofuran, which displayed excellent antibacterial activity in direct contact experiments. In this study, we observed that NFBC without antibiotic addition showed no inhibition zone (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Leaching experiments demonstrated that this bone cement did not release antibacterial components, yet it exhibited effective antibacterial properties against common clinical bacteria [ 14 ]. Similarly, Fu et al [ 16 ] developed a non-leaching antibacterial bone cement using nitrofuran, which displayed excellent antibacterial activity in direct contact experiments. In this study, we observed that NFBC without antibiotic addition showed no inhibition zone (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…All bone cement samples were composed of NFBC powder and methyl methacrylate (MMA) liquid monomer in a 2:1 ratio. The NFBC was prepared using literature-reported methods [ 16 ]. Briefly, p(10% NFMA-co-MMA) is obtained by polymerization of 10% 5-nitrofurfuryl alcohol methacrylate (NFMA) with MMA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 However, recent studies have shown that PMMA bone cements loaded with the first-line anti-tuberculosis drugs like isoniazid (INH) not only suffer from disadvantages related to the traditional antibiotic-loaded bone cement (ALBC) burst release, but the mechanical strength is also significantly reduced, far below the ISO standard of 70 MPa. [14][15][16][17][18] Progress has been made in the research of novel materials through innovative approaches to combining drugs, bioactive nanoparticles with implantable polymers, aiming to reduce burst release, extend release duration, and enhance the mechanical strength after the incorporation of antibiotics. 13,[19][20][21][22][23][24][25][26][27][28][29][30] High density polyethylene containing non-covalently doped antibiotics which formed under high pressure can continue to release the drug for up to three weeks, but this excellent material is preformed and therefore not injectable.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 However, recent studies have shown that PMMA bone cements loaded with the first-line anti-tuberculosis drugs like isoniazid (INH) not only suffer from disadvantages related to the traditional antibiotic-loaded bone cement (ALBC) burst release, but the mechanical strength is also significantly reduced, far below the ISO standard of 70 MPa. 14–18…”
Section: Introductionmentioning
confidence: 99%